Impure Prosocial Motivation in Charity Provision: Warm-Glow Charities and Implications for Public Funding - Kimberley Ann Scharf (Center for Economic Studies and ifo Institute (CESifo), 2013)
We show that warm-glow motives in provision by competing suppliers can lead to inefficient charity selection. In these situations, discretionary donor choices can promote efficient charity selection even when provision outcomes are non-verifiable. Government funding arrangements, on the other hand, face verification constraints that make them less flexible relative to private donations. Switching from direct grants to government subsidies for private donations can thus produce a positive pro-competitive effect on charity selection, raising the value of charity provision per dollar of funding.
Keywords: H20; H30; H40; L30; 330; private provision of public goods; warm glow; tax incentives for giving; competition in the nonprofit sector